The impossible state : North Korea, past and future - Cha, Victor D., 1961- (New York : Ecco, 2012)
Looks at the nation of North Korea, its history, social conditions, and place in world politics as it stands today and where it is likely to end up in the future.
Glossary of acronyms and abbreviations -- Contradictions -- The best days -- All in the family -- Five bad decisions -- The worst place on Earth -- The logic of deterrence -- Complete, verifiable, and irreversible dismantlement (CVID) -- Neighbors -- Approaching unification -- The end is near.
Includes index and bibliography : p. [469]-506.
Keywords: Culture politique -- Coree du Nord -- Histoire; Coree du Nord -- Politique et gouvernement; Coree du Nord -- Relations exterieures -- Etats-Unis.; Etats-Unis -- Relations exterieures -- Coree du Nord; Coree du Nord -- Conditions sociales